Angiotensin II Decreases Endothelial Nitric Oxide Synthase Phosphorylation via AT1R Nox/ROS/PP2A Pathway - Ding, Jing; Yu, Min; Jiang, Juncai; Luo, Yanbei; Zhang, Qian; Wang, Shengnan; Yang, Fei; Wang, Alei; Wang, Lingxiao; Zhuang, Mei; Wu, Shan; Zhang, Qifang; et al. (Frontiers in Physiology, 2020)
Increasing evidences suggest that angiotensin (Ang) II participates in the pathogenesis of endothelial dysfunction through multiple signaling pathways including angiotensin type 1 receptor (AT1R) mediated NADPH oxidase (Nox)/reactive oxygen species (ROS) signal transduction. However, the detailed mechanism is not completely understood. In this study, we reported that AngII/AT1R-mediated activated protein phosphatase 2A (PP2A) downregulated eNOS phosphorylation via Nox/ROS pathway. AngII treatment reduced the levels of phosphorylation of eNOS Ser1177 and nitric oxide (NO) content along with phosphorylation of PP2Ac (PP2A catalytic subunit) Tyr307, meanwhile increased the PP2A activity and ROS production in human umbilical vein endothelial cells (HUVECs). These changes could be impeded by AT1R antagonist candesartan (CAN). The pretreatment of 10-8 M PP2A inhibitor okadaic acid reversed the levels of eNOS Ser1177 and NO content. Similar effects of AngII on PP2A and eNOS were also observed in the mesenteric arteries of Sprague-Dawley rats subjected to AngII infusion via osmotic minipumps for 2 weeks. We found that the PP2A activity was increased, but the levels of PP2Ac Tyr307 and eNOS Ser1177 as well as NO content were decreased in the mesenteric arteries. The pretreatments of antioxidant N-acetylcysteine (NAC) and apocynin (APO) abolished the drop of the levels of PP2Ac Tyr307 and eNOS Ser1177 induced by AngII in HUVECs. The knockdown of p22phox by siRNA gave rise to decrement of ROS production and increment of the levels of PP2Ac Tyr307 and eNOS Ser1177. These results indicated that AngII/ AT1R pathway activated PP2A by downregulating its catalytic subunit Tyr307 phosphorylation which rely on the Nox activation and ROS production. In summary, our findings indicate that AngII downregulates PP2A catalytic subunit Tyr307 phosphorylation to activate PP2A via AT1R-mediated Nox/ROS signaling pathway. The activated PP2A further decreases levels of eNOS Ser1177 phosphorylation and NO content leading to endothelial dysfunction.